Aggressive Adaptive Beamforming for Ambient Noise Inversion with a Limited-Aperture Sonar on an Autonomous Platform - Arvelo, Juan (Proceedings of meetings on acoustics, 2008)
Bottom loss inference from ambient noise inversion has been shown to yield accurate and robust predictions of undersea sound propagation and sonar detection performance using vertical line arrays and a conventional beamformer [Arvelo, J. Acoust. Soc. Am., 123, 679, 2008]. However, any array with a vertical aperture should be good candidates for ambient noise inversion. The main problem with vertical line arrays is that they are not well suited to rapidly survey a large area. Platform translation with a vertical array is expected to cause extreme array shape distortions that could seriously limit the accuracy of the results. To mitigate array shape distortion, a smaller array with vertical aperture could be mounted on the survey platform, which would allow it to survey the area at greater speeds. The platform's diameter certainly limits the vertical aperture of the array. A limited vertical aperture limits the frequency range, resolution, and accuracy of the estimated bottom loss. Since the array is rigidly fixed to the platform's body, an aggressive adaptive beamformer may be adopted to increase the resolution and accuracy of the inverted bottom loss to very low frequencies. The performance is demonstrated via comparisons against conventional beamformers with numerical simulations and measurements.